2016
DOI: 10.1111/jcmm.12843
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in female reproductive system (human and animal)

Abstract: Telocytes (TCs) are a newly discovered type of cell with numerous functions. They have been found in a large variety of organs: heart (endo‐, myo‐, epi‐ and pericardium, myocardial sleeves, heart valves); digestive tract and annex glands (oesophagus, stomach, duodenum, jejunum, liver, gallbladder, salivary gland, exocrine pancreas); respiratory system (trachea and lungs); urinary system (kidney, renal pelvis, ureters, bladder, urethra); female reproductive system (uterus, Fallopian tube, placenta, mammary glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…1 The quantity of TCs in the endometrium and the myometrium correlates with the reproductive state. 40 Immature rat uteruses present the lowest density of TCs compared to pregnant and postpartum ones. 41 The number of endometrial TCs in pregnant state increases, while there is a reduction of their number in the myometrium.…”
Section: Telocytes In Uterusmentioning
confidence: 95%
See 3 more Smart Citations
“…1 The quantity of TCs in the endometrium and the myometrium correlates with the reproductive state. 40 Immature rat uteruses present the lowest density of TCs compared to pregnant and postpartum ones. 41 The number of endometrial TCs in pregnant state increases, while there is a reduction of their number in the myometrium.…”
Section: Telocytes In Uterusmentioning
confidence: 95%
“…41 The number of endometrial TCs in pregnant state increases, while there is a reduction of their number in the myometrium. 40 Hence, changes in the quantity of TCs in the myometrium may be associated with the prevention of preterm delivery. 25 Moreover, the highest number of myometrial TCs were found in the postpartum uteri, which may be related with its involution.…”
Section: Telocytes In Uterusmentioning
confidence: 99%
See 2 more Smart Citations
“…Tcs simultaneously belong to interstitial, endothelial, smooth muscle, nerve, mast, and hematopoietic stem cell immunophenotypes. They express CD117, vimentin, CD34, SMA, S100, NSE, as well as the gap junction protein connexin-43 [5,6,7]. Tcs form a 3D network in almost all organs, and they are involved in inflammation, regeneration, and angiogenesis; through multiple diverse cell-to-cell contacts and micro-vesicle involvement, they can coordinate inter-cellular interactions [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%